2022
DOI: 10.3390/curroncol29050243
|View full text |Cite
|
Sign up to set email alerts
|

The Chemo-Gut Pilot Study: Associations between Gut Microbiota, Gastrointestinal Symptoms, and Psychosocial Health Outcomes in a Cross-Sectional Sample of Young Adult Cancer Survivors

Abstract: Chemotherapy adversely affects the gut microbiota, inducing dysbiosis, and negatively impacts gastrointestinal (GI) and psychosocial health during treatment, but little is known about the long-term effects or how these factors are related. Methods: This cross-sectional pilot study investigated the effects of chemotherapy on the gut microbiota, GI symptoms, and psychosocial outcomes in cancer survivors aged 18–39 years old, compared to healthy controls. Gut microbial diversity and composition were assessed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Moreover, neither study incorporated baseline measurements of richness before starting chemotherapy treatment, so it is not possible to determine whether the observations represent a post-treatment decrease in richness. In addition to the findings above, Deleemans et al 31 found that microbiome richness was negatively associated with depressive and cognitive symptoms. To note, individuals receiving frequent chemotherapy over a long period of time may be most susceptible to incomplete microbiome recovery and thus higher systemic inflammation.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Moreover, neither study incorporated baseline measurements of richness before starting chemotherapy treatment, so it is not possible to determine whether the observations represent a post-treatment decrease in richness. In addition to the findings above, Deleemans et al 31 found that microbiome richness was negatively associated with depressive and cognitive symptoms. To note, individuals receiving frequent chemotherapy over a long period of time may be most susceptible to incomplete microbiome recovery and thus higher systemic inflammation.…”
Section: Discussionmentioning
confidence: 76%
“…This supports established literature denoting that microbiome richness decreases following perturbations such as chemotherapy 17,29 and antibiotics 30 and returns toward the baseline after time. A recent study 31 reported that cancer survivors less than 6 months since their last treatment had lower richness than both cancer survivors more than 6 months since their last treatment, and healthy controls. Unfortunately our study did not assess duration or frequency of chemotherapy treatment, which could have ramifications for whether or not the microbial communities could fully recover between treatments, given that repeated and frequent perturbations increase the risk of incomplete community recovery 30 .…”
Section: Discussionmentioning
confidence: 94%
“…A subset of demographic and health survey questions were taken from a locally developed questionnaire used in the Chemo-Gut Pilot Study. 19 These questions were developed based on patient engagement, feedback from the cancer community, and coauthor expertise. Patient demographics included 8 items regarding current age, sex, ethnicity, education, marital status, community (ie rural or metropolitan), income, and Canadian province.…”
Section: Methodsmentioning
confidence: 99%
“… 6 , 20 In both human and animal studies, chemotherapy has been shown to induce a dysbiotic state which may contribute to treatment-related toxicities. 19 , 21 24 The current literature mainly focuses on gut dysbiosis and physical treatment-related symptoms. However, as adverse psychological and cognitive side-effects of cancer treatments are also frequently reported by people with cancer, research must shift to include the investigation of potential mechanisms driving these symptoms, such as dysbiosis of the gut microbiota or neurotoxic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have implicated the gut microbiota, and in some cases specific microbes, in successful response to various chemotherapies [ 8 , 9 , 34 , 35 ], suggesting similar mechanisms may support successful response to common breast cancer chemotherapeutics. Additionally, improved gut microbial profiles during or after treatment may help mitigate individuals’ increased risk for developing obesity or anxiety, depression, or fear of recurrence through favorable metabolic profile alterations [ 36 , 37 ] and the gut–brain axis [ 38 , 39 , 40 , 41 , 42 ] respectively. Up to 17% of those diagnosed with stage I and II breast cancer, 62% with stage III, and 66% with stage IV will undergo chemotherapy during their treatment [ 43 ].…”
Section: Introductionmentioning
confidence: 99%